2020
DOI: 10.1073/pnas.2004761117
|View full text |Cite
|
Sign up to set email alerts
|

Hemolymph protease-5 links the melanization and Toll immune pathways in the tobacco hornworm, Manduca sexta

Abstract: Proteolytic activation of phenoloxidase (PO) and the cytokine Spätzle during immune responses of insects is mediated by a network of hemolymph serine proteases (HPs) and noncatalytic serine protease homologs (SPHs) and inhibited by serpins. However, integration and conservation of the system and its control mechanisms are not fully understood. Here we present biochemical evidence that PO-catalyzed melanin formation, Spätzle-triggered Toll activation, and induced synthesis of antimicrobial peptides are stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…Recognition of pathogens or parasites activates serine proteases, enzymes in hemolymph that activate PPOs into POs by proteolytic cleavage. POs launch a train of serine protease activation reactions that lead to synthesis of melanin, an important component of insect immunity [ 60 ]. Melanin can be deposited on newly formed hemocyte nodules and on parasites after hemocyte encapsulation, where, as a chemically active compound, it helps kill pathogens.…”
Section: Eicosanoid Actions In Insect Immunitymentioning
confidence: 99%
“…Recognition of pathogens or parasites activates serine proteases, enzymes in hemolymph that activate PPOs into POs by proteolytic cleavage. POs launch a train of serine protease activation reactions that lead to synthesis of melanin, an important component of insect immunity [ 60 ]. Melanin can be deposited on newly formed hemocyte nodules and on parasites after hemocyte encapsulation, where, as a chemically active compound, it helps kill pathogens.…”
Section: Eicosanoid Actions In Insect Immunitymentioning
confidence: 99%
“…In insects, Toll receptor is activated by binding to its ligand, Spätzle, which is activated by sequential activation of serine proteases after pathogen recognition [19]. This led us to pose a PLOS PATHOGENS hypothesis that DSP1 acts as an initial immune inducer by activating the Toll-Spätzle signal pathway to activate PLA 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis showed that O. furnacalis serpin–4 clustered together with B. mori serpin–4, M. sexta serpin–4, Operophtera brumata serpin–4 and Plutella xylostella serpin–4, with the bootstrap value of 100 ( Figure S4 ). Among them, M. sexta serpin–4 has been verified experimentally to inhibit PPO activation by inhibiting at least 4 target serine proteases ( 27 , 45 ). Therefore, we predicted that O. furnacalis serpin–4 could also function as an inhibitor of melanization response.…”
Section: Resultsmentioning
confidence: 99%